Diabetes mellitus and echocardiographic left ventricular function in free-living elderly men and women: The Cardiovascular Health Study. - Lee, M; Gardin, J M; Lynch, J C; Smith, V E; Tracy, R P; Savage, P J; Szklo, M; Ward, B J (Am Heart J, 1997)
This report describes the relation among diabetes, blood pressure, and prevalent cardiovascular disease, and echocardiographically measured left ventricular mass and filling (transmitral valve flow) velocities in the Cardiovascular Health Study, a cohort of 5201 men and women > or = 65 years of age. Ventricular septal and left posterior wall thicknesses were greater in diabetic than in nondiabetic subjects, showing a significant linear trend (p = 0.025 for ventricular septal thickness in both sexes combined, p = 0.002 for posterior wall thickness) with increased duration of diabetes. Increased wall thickness of the ventricular septum or the left posterior wall was not associated with prevalent coronary heart disease (CHD) in the cohort. Increased left ventricular mass was associated with diabetic persons not reporting CHD and with all subjects with CHD regardless of glucose tolerance status. After adjusting for body weight, blood pressure, heart rate, and prevalent coronary or cerebrovascular disease, diabetes (as measured by glucose level, insulin use, oral hypoglycemic use, and a positive history of diabetes before baseline examination) remained an independent predictor of increased left ventricular mass among men and women (174.2 gm in diabetic men vs 169.8 gm in normal men, 138.2 gm in diabetic women vs 134.0 gm in normal women, p = 0.043 for both sexes combined). Both early and late diastolic transmitral peak flow velocities were higher with increased duration of diabetes, but the calculated ratio of the early peak flow velocity to the late velocity (E/A ratio) did not differ significantly between subjects with historical diabetes and those with normal fasting glucose (both genders combined, p = 0.190). Glucose level, insulin use, oral hypoglycemic use, and a positive history of diabetes before baseline examination were significant independent predictors of the late transmitral peak flow velocity and its integrated flow-velocity curve but not for the integral of the early peak flow velocity or the E/A ratio. Diabetes is associated with abnormal left ventricular structure and function in elderly persons. This association persists after adjustment for body weight, blood pressure, heart rate, and reported coronary or cerebrovascular disease.
Keywords: Aged; Blood Flow Velocity; Blood Pressure; Diabetes Mellitus; Echocardiography; Female; Glucose Tolerance Test; Humans; Male; Mitral Valve; Residence Characteristics; Ventricular Function, Left